What is the best adjustment of appendicular lean mass for predicting mortality or disability among Japanese community dwellers? - Otsuka, Rei (BMC Geriatr, 2018)
BACKGROUND: Age-related declines in skeletal muscle mass and strength, representing “sarcopenia,” are a growing concern in aging societies. However, the prevalence of low muscle mass based on the height(2)-adjustment has been shown to be extremely low, and a more appropriate definition of low muscle mass is needed, particularly for Asian women. The aim of this study was to explore the most appropriate adjustment of appendicular lean mass (ALM) for predicting mortality or disability risk using ALM or any of 5 adjustments of ALM among community-dwelling Japanese. METHODS: Subjects comprised 1026 men and 952 women between 40 and 79 years old at baseline (1997–2000) who participated in the National Institute for Longevity Sciences - Longitudinal Study of Aging, Japan. ALM (kg) and 5 adjusted indices of ALM (ALM/leg length, ALM/height, ALM/height(2), ALM/weight, and ALM/body mass index [BMI]) were assessed at baseline. Disability was defined by long-term care insurance certification based on responses to a survey mailed in 2013, and death records were obtained as vital statistics until December 2014. Crude and adjusted Cox proportional hazard models were used to estimate hazard ratios for mortality or disability by sex-stratified quintiles of each ALM index (ALM and adjusted ALM) or sarcopenia-related indices. The area under the curve (AUC) was calculated with the multivariate-adjusted logistic regression model. Additionally, mixed-effects analyses were used to clarify the age-related ALM indices decline over 12 years (n = 1838). RESULTS: Crude Cox proportional hazard models and multivariate-adjusted logistic model (AUC) indicated that higher ALM and ALM/BMI in women, and higher ALM, ALM/leg length, ALM/height, and ALM/BMI in men were associated with lower risks for mortality or disability than ALM/height(2). The mixed effect model indicated all ALM indices in men, and ALM, ALM/leg length, and ALM/height in women could better predict age-related lean muscle mass decline. CONCLUSIONS: Unadjusted ALM in women, and ALM/leg length, ALM/height, ALM/BMI, and ALM in men may be more appropriate for predicting future mortality or disability than ALM/height(2). Considering the age-related muscle mass decline, unadjusted ALM would be the first variable to assess, regardless of sex, in this Japanese cohort study. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12877-017-0699-6) contains supplementary material, which is available to authorized users.